Acromegaly, Herniation of Cerebellar Tonsils, and Arnold–Chiari 1 Malformation: The Importance of Right Definitions - Alessandro Ciarloni; Gianmaria Salvio (Case Reports in Endocrinology)
We present a case of acromegaly associated with Arnold–Chiari 1 malformation and a literature review regarding this association, mainly focusing on the importance of a clear distinction between Chiari malformation and herniation of cerebellar tonsils (CTH). Indeed, in many clinical cases, this distinction has not been properly made and a better description of the radiological findings could be important for the clinical management of these patients. In fact, Arnold–Chiari 1 malformation, as a congenital disease, is not caused by acquired growth hormone (GH) excess, but the latter could worsen pre-existing CTH or even induce it ex novo. Therefore, awareness of this condition in the clinical management of acromegaly appears crucial.